CLASSIFICATION OF THE LEVEL OF ACTIVITIES IM PILATES PRACTITIONERS (CIPEEX, 2022)
OBJECTIVE: ASSESS AND PRESENT THE LEVEL OF PHYSICAL ACTIVITY OF THE PILATES PRACTITIONERS. METHODS: ITS ABOUT AN ASSESSMENT WHERE IT WAS APPLIED THE INTERNATIONAL PHYSICAL ACTIVITY QUESTIONNAIRE ( IPAQ ) IN PRINTED FORM TO THE STUDENTS OF A PILATES STUDIO IN THE CITY OF GOIANSIA GO, WHERE 20 ADULT INDIVIDUALS WERE EVALUATED AFTER YOUR CLASSES. THE QUESTIONNAIRE CONTAINED ITEMS FOR EVALUATION BEING VERY ACTIVE, ACTIVE, IRREGULARLY ACTIVE A, IRREGULARLY ACTIVE B, AND SEDENTARY. IN THIS WORK, THE COLLECTED DATA WERE GROUPED INTO A TABLE AND TRANSFORMED INTO A FIGURE BY THE PROGRAM MICROSOFT EXCEL. WITH THE ANALYSIS OF FIGURE, THE PRESENT WORK WAS PRODUCED. RESULTS: OF THE 20 STUDENTS WHO PARTICIPATED IN THE ASSESSMENT, THE AVERAGE AGE WAS 45,6 NONE WERE CLASSIFIED AS SEDENTARY AND 10% WERE VERY ACTIVE. IN THE VERY ACTIVE GROUP, ONLY MEN STOOD OUT AND AT WORK THERE WAS NO SEDENTARY PERSON. CONCLUSIONS: THIS STUDY MADE IT POSSIBLE TO ASSESS PHYSICAL CAPACITY AND NOTE THAT REGULAR PRACTICE OF PILATES INCREASES THE LEVEL OF PHYSICAL ACTIVITY OF THE EVALUATED INDIVIDUALS, BEING ABLE TO HIGHLIGHT IF THE NEED FOR PILATES TO OBTAIN A MORE ACTIVE LIFE AND DELAYING THE ONSET OF COMPLICATIONS, ONE OF THEM BEING THE LACK OF JOINT MOBILITY.